New Insights of Phospholipase A2 Associated Neurodegeneration Phenotype Based on the Long-Term Follow-Up of a Large Hungarian Family - Toth-Bencsik, Renata; Balicza, Peter; Varga, Edina Timea; Lengyel, Andras; Rudas, Gabor; Gal, Aniko; Molnar, Maria Judit (Frontiers in Genetics, 2021)
Abstract Introduction: Phospholipase A2-associated Neurodegeneration (PLAN) is a group of neurodegenerative diseases associated with the alterations of the PLA2G6 gene. Some phenotype-genotype association are well known but there is no clear explanation why some cases can be classified into distinct subgroups, while others follow a continuous clinical spectrum. Methods: Three affected girls and their family were investigated. Long-term neurological, and psychiatric follow-up, neuropathological, radiological, and genetic examinations, were performed. Results: The three affected sisters harboured the p.P622S, and p.R600W mutation in PLA2G6. The age of onset and the most prominent presenting symptoms (vertical gaze palsy, ataxia, dystonia, psychomotor regression indicated that all children have atypical neuroaxonal dystrophy (ANAD), however optic atrophy, severe tetraparesis, and the iron accumulation in both the globus pallidus and substantia nigra would fit into the subgroup classical infantile neuroaxonal dystrophy (INAD). The slow progression, the rigidity, bradykinesis, and the prominent psychiatric symptoms indicate PLA2G6-related dystonia-parkinsonism (DP). Abnormal mitochondria, lipid accumulation and axonal spheroids were observed in the muscle and nerve tissue. Mild MRI alterations were detected in the asymptomatic carrier parents. Conclusion: The colourful symptoms, the slightly discordant clinical picture in the identical twins and the neuroimaging data suggest the hypothesis that in PLA2G6 associated disorders even with the same mutation might associate with a spectrum of clinical syndromes and the phenotype does not always fit into the classical subgroups of the disease. The mild MRI alterations of the asymptomatic parents and the family history might indicate that even heterozygous variants are not completely silent clinically.